Wisdom in Ahmad Shoughi & Parvin E’tesami’s Allegorical Poem - Afra, Mansour; Mirghaderi, Seyyed Fazlollah (LANGUAGE ART, 2023)
Wise poem is one of most important poetic subjects in Persian & Arabic, and in various periods, a number of poets have written convenient poems. Ahmad Shoughi & Parvin E’tesami have given wisdom in allegories and fables. In this paper, some of wise stories written by those poets, are allegorical which have been analyzed comparatively and stated collective and distinguished aspects. Finally this is resulted that after telling fables and creating animal characters, Shoughi has tried make your opinion. But Parvin has been stated wisdom in allegorical way and it is reader that have to make her or his own opinion. Guidance of people to welfare by preaching and dispersion of wisdom, moral values are aims of both poets.